Effect of Hydrogel Containing Achyrocline satureioides (Asteraceae) Extract-Loaded Nanoemulsions on Wound Healing Activity - Lucélia Albarello Balestrin; Patrícia Inês Back; Magno da Silva Marques; Gabriela de Moraes Soares Araújo; Mariana Corrêa Falkembach Carrasco; Matheus Monteiro Batista; Tony Silveira; Jamile Lima Rodrigues; Flávia Nathiely Silveira Fachel; Leticia Scherer Koester; Valquiria Linck Bassani; Ana Paula Horn; et al. (MDPI AG, 2022)
Achyrocline satureioides (Lam.) DC extract-loaded nanoemulsions have demonstrated potential for wound healing, with promising effects on keratinocyte proliferation. We carried out the first in vivo investigation of the wound healing activity of a hydrogel containing A. satureioides extract-loaded nanoemulsions. We prepared hydrogels by adding the gelling agent (Carbopol® Ultrez) to extract-loaded nanoemulsions (~250 nm in diameter) obtained by spontaneous emulsification. The final flavonoid content in formulation was close to 1 mg/mL, as estimated by ultra-fast liquid chromatography. Permeation/retention studies using porcine ear skin showed that flavonoids reached deeper layers of pig ear skin when it was damaged (up to 3.2 µg/cm² in the dermis), but did not reach the Franz-type diffusion cell receptor fluid. For healing activity, we performed a dorsal wound model using Wistar rats, evaluating the lesion size, anti-inflammatory markers, oxidative damage, and histology. We found that extract-loaded formulations promoted wound healing by increasing angiogenesis by ~20%, reducing inflammation (tumor necrosis factor α) by ~35%, decreasing lipid damage, and improving the re-epithelialization process in lesions. In addition, there was an increase in the number of blood vessels and hair follicles for wounds treated with the formulation compared with the controls. Our findings indicate that the proposed formulation could be promising in the search for better quality healing and tissue reconstruction.